A 2D imaging system for mapping luminescence-depth profiles for rock surface dating. (January 2022) - Sellwood, E.L.; Kook, M.; Jain, M.
Abstract: Spatially resolved optically stimulated luminescence (OSL) offers a means for rapid assessment of dose distributions in retrospective dosimetry and geochronology. Until recently, OSL imaging systems have largely been restricted to measurements of millimetre scale samples; this approach is not well suited for applications where the physical process of interest operates on centimetre scale (e.g., depth dependent trap eviction in exposed rocks, sediment mixing in soils, attenuation of gamma radiation, etc.). Here we describe and demonstrate the Risø Luminescence Imager - an electron multiplying charge-coupled device (EMCCD) based imaging system for measuring infrared photoluminescence (IRPL) and infrared stimulated luminescence (IRSL) from centimetre scale samples. While these signals specifically arise from feldspar, the stimulation and detection configuration may be modified to suit other target materials/dosimeters. We characterise the stability and reproducibility of the system through IRPL and IRSL measurements from a large (∼4 × 5 cm) heterogeneous rock sample, and a slice of K-feldspar mineral. Finally, we present examples of suitable applications, including the reconstruction of luminescence-depth profiles from IRPL and IRSL images, and reconstruction of IRSL decay curves. Measurement of luminescence-depth profiles with high resolution using 2D imaging using the Risø Luminescence Imager is expected to improve our understanding of the trap emptying mechanisms (kinetics) in rocks. This system also opens new avenues for the development of field imaging instrumentation and provides opportunity to study feldspar luminescence in relation to its geochemistry. Graphical abstract: The stability of each light source was assessed by measuring light intensity as a function of time directly through using either a photodiode (Ophir Starlight power meter) placed in the centre of the sample stage (for the 830 nm laser and 850 nm LEDs), or through imaging time-series of the illumination area on a white paper using EMCCD (for the 532 nm laser and 885 nm laser). In the latter case, the mean value of a central region of each frame was used for constructing the series. Highlights: EMCCD-based instrument for imaging of large cm-scale rock surfaces. IRPL at 955 nm and 880 nm and IRSL at room temperature. Rapid measurements at high (0.17 mm) resolution of luminescence from feldspars. Applications from rock surface dating, equivalent dose determination and geochemical assessments.